Ecological and evolutionary constraints on regional avifauna of passerines in China. Issue 4 (15th December 2020) - Cai, Tianlong; Quan, Qing; Song, Gang; Wu, Yongjie; Wen, Zhixin; Zhang, Chunlan; Qu, Yanhua; Qiao, Gexia; Lei, Fumin
Abstract: Strong correlations between species diversity and climate have been widely observed, but the mechanism underlying this relationship is unclear. Here, we explored the causes of the richness–climate relationships among passerine birds in China by integrating tropical conservatism and diversification rate hypotheses using path models. We found that assemblages with higher species richness southwest of the Salween–Mekong–Pearl River Divide are phylogenetically overdispersed and have shorter mean root distances (MRDs), while species-rich regions northeast of this divide (e.g., north Hengduan Mountains–south Qinling Mountains) are phylogenetically clustered and have longer MRDs. The results of the path analyses showed that the direct effect of climatic factors on species richness was stronger than their indirect effects on species richness via phylogenetic relatedness, indicating that neither tropical conservatism nor diversification rate hypotheses can well explain the richness–climate relationship among passerines in China. However, when path analyses were conducted within subregions separately, we found that the tropical conservatism hypothesis was well supported in the southwestern Salween–Mekong–Pearl River Divide, while the diversification rate hypothesis could explain the richness–climate relationship well in the northeastern divide. We conclude that the diversity patterns of passerines in different subregions of the Eastern Himalayas-Mountains of Southwest China may be shaped by different evolutionary processes related to geological and climatic histories, which explains why the tropical conservatism or diversification rate hypothesis alone cannot fully explain the richness–climate relationships.